Evaluation of the nasal contractility capacity in postmenopausal women - Yildirim, Yavuz Selim; Senturk, Erol; Tugrul, Selahattin; Ozturan, Orhan (Rhinology, 2014)
The aim of this study was to objectively compare nasal contractility in premenopausal and postmenopausal patients by means of rhinomanometry, acoustic rhinometry, and peak inspiratory nasal flow. Design: prospective, clinical case-controlled study. Setting: university tertiary-care hospital, referral center. Participants: the study included 97 participants divided into two groups: 49 postmenopausal (the study group) and 48 premenopausal (control) females. Nasal evaluations were made utilizing anterior rhinoscopy, peak inspiratory nasal flow, acoustic rhinometry, and anterior rhinomanometry. The differences between before and after decongestant application of Minimal Cross-sectional Area (MCA) 1, Minimal Cross-sectional Area (MCA) 2, Peak inspiratory nasal flow (PNIF), Rhinomanometry (RMM), Flow, and Volume values were been statistically significant in both postmenopausal and premenopausal group (control). Before and after all the subjects were administered nasal decongestant, nasal contractility was evaluated using objective nasal tests (acoustic rhinometry, rhinomanometry, and peak inspiratory nasal flow. Results showed that erectile tissues were not affected after menopause: postmenopausal women have the same nasal contractility capacity as premonopausal women.